Exhibition Reviews. (1st June 2015) - Frascina, Francis; Barbu, Adam; Lehtinen, Heini; Pecorari, Marco; Springgay, Stephanie; Suslau, Dzmitry
LOVE IS ENOUGH: WILLIAM MORRIS & ANDY WARHOL Curated by Jeremy Deller, Modern Art Oxford, 6 December 2014 – 8 March 2015CHRISTIAN BOLTANSKI, ALMAS Curated by Beatriz Bustos, Museo Nacional de Bellas Artes, Santiago, Chile, 30 October 2014 – 4 January 2015BIO 50 – 24TH BIENNIAL OF DESIGN LJUBLJANA Curated by Jan Boelen, Maja Vardjan and Cvetka Požar, Museum of Architecture and Design, Museum of Modern Art, and eighteen other locations, Ljubljana, 18 September – 7 December 2014OLIVIER SAILLARD AND TILDA SWINTON, THE CLOAKROOM – VESTIAIRE OBLIGATOIRE Musée de la Mode de Paris Galliera, Paris, 22–29 November 2014CENTRE FOR INCIDENTAL ACTIVISMS (CIA) #2 Orchestrated by Emelie Chhangur, Suzanne Carte, Michael Maranda and Allyson Adley, and co-organized with Maggie Flynn, Ame Henderson, Jp King and Terrarea, Art Gallery of York University, Toronto, 6 January – 2 March 2014FISCHLI/WEISS, ROCK ON TOP OF ANOTHER ROCK Curated by Hans-Ulrich Obrist and Julia Peyton-Jones, Serpentine Galleries, London, 7 March 2013 – 30 September 2014